Cost control framework for building contractors in minimising the cost variance / Shariffah Zatil Hidayah Syed Jamaludin - Syed Jamaludin, Shariffah Zatil Hidayah (2014)
Construction industry is a risky business due to the involvement of the large amount of money for every construction activities. Recently it was reported that even though there is various availability of cost control techniques and project control software in the construction industry, most of the projects still does not achieve their stipulated budget. Thus, the aim of this study will look into developing a framework of cost control in minimising the cost variance during the construction stage. The study was carried out by investigating the current cost control practices among building contractors, analysing major causes of cost variance and recommend the appropriate measures on cost control to minimise the cost variance. A total of 320 questionnaires were sent to G7/Class A building contracting firms within the Klang Valley and followed by interviews among the eight (8) construction experts. Data collected from the questionnaire surveys and interviews were analysed by using Statistical Package for Social Sciences Software (SPSS 20.0) and interview coding system. The study shows that the majority of the building contractors faced problems in poor management of cost control techniques due to the lack of technical experience and insufficient of construction cost data. Three major causes of cost variance during the construction stage were identified ranges from site management group, design and documentation group and material management group. Ultimately, the outcomes of this research will hopefully help to develop cost management framework as a guideline to improve the project execution and deliverable performance construction projects in Malaysia.